Problem or opportunity? Immigration, job search, entrepreneurship and labor market outcomes of natives in Germany - Zainab Iftikhar; Anna Zaharieva (Bielefeld University, Faculty of Business Administration and Economics, 2024)
In this study we evaluate the effects of low-skilled immigration on small businesses, wages and employment in Germany. We develop a search and matching model with heterogeneous workers, cross-skill matching, and endogenous entry into entrepreneurship. The model is calibrated using German Socio-Economic Panel (SOEP) data. Quantitative analysis shows that low-skilled immigration benefits high-skilled workers while negatively affecting the welfare of low-skilled workers. It leads to the endogenous expansion of immigrant entrepreneurial activities, generating positive spillovers for all demographic groups except native entrepreneurs. Overall, there is a marginal loss to the economy in terms of per worker welfare. This loss is mitigated with increased skilled migration from India. Policies restricting immigrant entrepreneurship relax competition for native small businesses but reduce welfare for all other worker groups. Ethnic segregation of small businesses benefits low-skill native entrepreneurs.
urn:nbn:de:0070-pub-29994434
Keywords: J23; J31; J61; J64; L26; 330; entrepreneurship; small business; self-employment; search frictions; immigration